HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN KEPEMIMPINAN PADA SISWA KELAS 10 DI SMK NEGERI 1 LIMBOTO - Martesya S S Keki; Lenny Syamsuddin; Fendi Ntobuo (LPPM Universitas Muhammadiyah Gorontalo, 2026)
Student leadership is becoming increasingly important in response to the complexity of social and academic challenges. An effective leader needs to build harmonious relationships, motivate others, and effectively manage conflict, all components of emotional intelligence. The research question is whether there is a relationship between emotional intelligence and leadership. This study aims to investigate the relationship between emotional intelligence and leadership. This research was conducted at SMK Negeri 1 Limboto, using a quantitative correlational design. The sampling technique used was total sampling, with 82 10th-grade students as subjects. This study used a Pearson product-moment correlation. The findings of this study showed a significant value of 0.000 (p